Evaluation of the Insecticidal Properties of Cassia alata L. Against Cowpea Weevil, Callobruchus maculatus Fab. (Coleoptera: Bruchidae) - Olusola Michael Obembe; Joshua Kayode (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
A laboratory study was conducted to investigate the efficacy of powder and extract of C. alata on Callosobruchus maculatus Fab. damage in stored cowpea (Vigna unguiculata L.) seeds. The powder and the extract were evaluated on C. maculatus for mortality, oviposition and adult emergence effects. The long-term storage of the treated seeds was also investigated. All treatments recorded higher significant (p < 0.05) mortality than the experimental control. Highest mortality of 100 % was recorded in seeds treated with C. alata extract at the dosage level of 4.0 % v/w while highest mortality of 80.30 % was also recorded in seed treated with 4.0 g of C. alata powder. The powder and the extract significantly reduced oviposition and adult emergence in the treated seed. Adult emergence was totally suppressed in seeds treated with 3.0 % v/w and 4.0 % v/w. The powder and the extract also reduced infestation and subsequence damage of the treated seeds. No damage was recorded in seeds treated with 3.0 % v/w and 4.0 % v/w of the extract. The result obtained revealed that extract and powder of C. alata were effective in controlling C. maculatus and could be recommended as an alternative to synthetic insecticides.